The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/mc.23250
|View full text |Cite
|
Sign up to set email alerts
|

SALL4 promotes tumor progression in breast cancer by targeting EMT

Abstract: Sal‐like protein 4 (SALL4) is overexpressed in breast cancer and might contribute to breast cancer progression, but the molecular mechanism remains unknown. Here, we found that within a group of 371 ethnic Chinese breast cancer patients, SALL4 was associated with lower grade (P = .002) and progesterone receptor positivity (P = .004) for overall cases; lower Ki67 (P = .045) and high vimentin (P = .007) for luminal cases. Patients with high SALL4 expression in lymph node metastasis showed a significantly worse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Consistent with the previous results, in vivo studies indicated that vimentin regulation by SALL4 enhances EMT, mammosphere formation, and tumorigenicity. SALL4 deficiency reduced lung colonization in MDA-MB-231 cells [ 142 ] and was associated with triple-negative (ER-, PR-, and HER2-) phenotypes [ 143 ]. Nevertheless, a recent study from 371 breast cancer patients showed that SALL4 expression positively correlates with PR protein level.…”
Section: Sall Proteins In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the previous results, in vivo studies indicated that vimentin regulation by SALL4 enhances EMT, mammosphere formation, and tumorigenicity. SALL4 deficiency reduced lung colonization in MDA-MB-231 cells [ 142 ] and was associated with triple-negative (ER-, PR-, and HER2-) phenotypes [ 143 ]. Nevertheless, a recent study from 371 breast cancer patients showed that SALL4 expression positively correlates with PR protein level.…”
Section: Sall Proteins In Cancermentioning
confidence: 99%
“…Nevertheless, a recent study from 371 breast cancer patients showed that SALL4 expression positively correlates with PR protein level. PR was related to breast cancer stemness in vitro, similar to SALL4 [ 142 ]. For an extensive review on SALL4 and breast cancer, refer to [ 143 ].…”
Section: Sall Proteins In Cancermentioning
confidence: 99%
“…It was reported that silencing RPS7 using specific siRNA attenuates prostate tumor growth and migration, associated with upregulation in E-cadherin and downregulation in N-cadherin and Snail [50]. Sal-like 4 is a transcription factor that is upregulated in several types of cancers [51]. Research revealed that targeting Sal-like 4 with specific siRNA decreases proliferation and colony formation, and induces apoptosis in PCa C4-2 cells, likely through regulation of the expression of Bcl-2 and Bax [52].…”
Section: Sirna-mediated Cancer-associated Gene Silencing In Prostate Cancermentioning
confidence: 99%
“…Studies in cancer also indicated that overexpression of SALL4 can increase the proliferation, migration, and invasion of cancer cells through targeting epithelial mesenchymal transition (EMT) [ 26 , 28 , 29 ]. Moreover, high expression of SALL4 is related to low survival and has been noticed as a prognostic factor in the patients with BC and gliomas [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%